Use of information and communication technologies in an agroindustrial cooperative in Concórdia, Santa Catarina - Gregolin, Marcos Roberto Pires; Gregolin, Graciela Caroline; Soares, Caroline Monique Tietz; Grandi, Adriana Maria de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The sustainability of family farming properties goes through several stages, and can refer to the diversification of crops and agro-industrialization of primary products as two of them. To the extent that the farmer gets only deliver primary production to another agent in the production chain, it happens to come across challenges and barriers that previously did not know. Cooperatives of farmers present as an efficient alternative to assist producers in overcoming these difficulties. In this context it has been the Information and Communication Technologies (ICTs) as tools and applications to creatively face one of the main bottlenecks of family agroindustrialization: marketing. The objective of this study was to contextualize the limits and potential of the use of ICT in organizational management, marketing, communication and marketing in a cooperative. Therefore, there was a case study of exploratory and qualitative, through participant observation and semi-structured questionnaire. The cooperative in question was using ICTs aiming perform tasks of daily life in a fast and effective way. However, the cooperative agribusinesses, there was a greater fragility of farmers, especially the dependence of children for the use of ICT, lack of commitment, dedication and habit. The managers of the cooperative have endeavored to improve the use of ICT as well as to expand the use of these tools by their members, despite the difficulties faced, aiming not only better organization, but also reduced costs and increased marketing of the products.